Trends and determinants of exclusive and predominant breastfeeding practices for two decades (2000–2019) in Ethiopia - Hailemariam Mamo Hassen (Frontiers in Nutrition)
BackgroundEthiopia has had a long-standing national commitment to improving child health. However, evidence on trends in breastfeeding has remained fragmented, and there is a paucity of information on the impacts of breastfeeding policy on breast feeding practices and associated factors influencing it. This study examined trends and determinants of exclusive and predominant breastfeeding in the last two decades.MethodsThe study employed a retrospective observational design using Ethiopian Demographic and Health Surveys (EDHS2000-2019) dataset for children aged <6 months and their mothers. Data analyses were performed via SPSS version 25. Trend analysis and multivariable logistic regression analysis were used.ResultsExclusive and predominant breastfeeding practices have fluctuated inconsistently over the past two decades. Exclusive breastfeeding increased from 59.96% in 2000 to 66.01% in 2016 and then decreased to 59.86% in 2019. Predominant breastfeeding decreased from 40.04% in 2000 to 32.95% in 2016 and increased to 39.43% in 2019. Regional state, place of residence, and religion were significantly (p < 0.001) associated with the likelihood of practicing exclusive or predominant breastfeeding.ConclusionThese inconsistent trends and the complex interplay of various factors suggest the limited success of previous policies and strategies and highlight the need for further investigation and revisiting current policies for a more nuanced and targeted approach in future interventions.